Clinical Validation of a New Optical Biometer for Myopia Control in a Healthy Pediatric Population - Elena Martínez-Plaza; Ainhoa Molina-Martín; Alfonso Arias-Puente; David P. Piñero (MDPI AG, 2022)
To assess the clinical validation of the Myah device in a pediatric population by evaluating the repeatability of biometric evaluations and analyzing its agreement with the Myopia Master system. A total of 51 children (51 eyes) were enrolled. Repeated measurements of flat (K1) and steep (K2) corneal radius, white-to-white (WTW) distance and axial length (AL) were performed with the Myah device. The same parameters were obtained from a subgroup (30 eyes) with the Myopia Master for the agreement analysis. The repeatability was assessed using the intrasubject standard deviation (Sw) and the intraclass correlation coefficient (ICC). The agreement was analyzed using the Bland-Altman method and the paired Student t-test. The Sw was 0.018 D, 0.021 D, 0.071 mm and 0.017 mm for K1, K2, WTW and AL, respectively (ICC ≥ 0.971). The mean difference and limits of agreement when comparing instruments were −0.013 (−0.102/0.077) for K1 (p = 0.16), −0.058 (−0.127/0.012) for K2 (p < 0.001), 0.151 (−0.370/0.673) for WTW (p < 0.001) and 0.030 (−0.091/0.151) for AL (p = 0.009). In conclusion, the Myah device provides consistent measurements of corneal radius, WTW distance and AL in a healthy pediatric population, validating their usefulness in clinical practice. These measurements could be used interchangeably with those provided by the Myopia Master device, although with some caution.